Effect of hormone replacement therapy on the bone mass and urinary excretion of pyridinium cross-links - Pardini, Dolores Perovano; Sabino, Anibal Tagliaferri; Meneses, Ana Maria; Kasamatsu, Teresa; Vieira, José Gilberto Henriques (São Paulo Medical Journal, 2000)
CONTEXT: The menopause accelerates bone loss and is associated with an increased bone turnover. Bone formation may be evaluated by several biochemical markers. However, the establishment of an accurate marker for bone resorption has been more difficult to achieve. OBJECTIVE: To study the effect of hormone replacement therapy (HRT) on bone mass and on the markers of bone resorption: urinary excretion of pyridinoline and deoxypyridinoline. DESIGN: Cohort correlational study. SETTING: Academic referral center. SAMPLE: 53 post-menopausal women, aged 48-58 years. MAIN MEASUREMENTS: Urinary pyr and d-pyr were measured in fasting urine samples by spectrofluorometry after high performance liquid chromatography and corrected for creatinine excretion measured before treatment and after 1, 2, 4 and 12 months. Bone mineral density (BMD) was measured by dual energy X-ray absorptiometry (DEXA) before treatment and after 12 months of HRT. RESULTS: The BMD after HRT was about 4.7% (P < 0.0004); 2% (P < 0.002); and 3% (P < 0.01) higher than the basal values in lumbar spine, neck and trochanter respectively. There were no significant correlations between pyridinium cross-links and age, weight, menopause duration and BMD. The decrease in pyr and d-pyr was progressive after HRT, reaching 28.9% (P < 0.0002), and 42% (P < 0.0002) respectively after 1 year. CONCLUSIONS: Urinary pyridinoline and deoxypyridinoline excretion decreases early in hormone replacement therapy, reflecting a decrease in the bone resorption rate, and no correlation was observed with the bone mass evaluated by densitometry.